Hemostasis in Dentistry (Springer International Publishing, 2018)
This book offers a thorough, clinically oriented review of hemostasis and its impact on the practice of dentistry. Readers will gain a sound understanding of the pathophysiology of hemostasis and the pharmacology of antithrombotic and prothrombotic medications. Perioperative dental management strategies of value in patients with different congenital and acquired disorders of hemostasis are carefully explained, and the role of surgical techniques and local and topical agents in helping to minimize and control bleeding is described. Helpful instruction is also provided on the indications for antithrombotic medications and the management of patients receiving such therapy, including the risks of altering medications. As the number of available oral antithrombotic agents continues to increase, dentists will encounter significantly more patients receiving treatments that affect hemostasis. In presenting comprehensive, up-to-date information on hemostasis, hemostatic disorders, antithrombotic therapy, and safe dental management, this book will serve as a rich source of information and a useful guide for practitioners and students alike. .